Multi-Criteria Selection of the Preferred Protocol of Routing in Ad-Hoc Networks by Hierarchies Analysis Method - Безрук, В. М.; Семенець, В. В.; Yu Zheng; Guo Qiang; Kovshar, V.; Semenets, V. V.; Bezruk, V. M. (IJSR, 2019)
Wireless ad-hoc networks are mobile decentralized dynamic self-organizing networks that do not have a fixed structure. This technology of building a wireless network is relevant in situations where you need to quickly deploy a network in a territory with mobile nodes. This article discusses the features of applying the hierarchy analysis method for multi-criteria selection of the preferred routing protocol in ad-hoc networks from a number of options.
Keywords: routing protocol; ad-hoc networks; hierarchy analysis method